A waste heat recovery strategy and its deployment: an integrated steelworks case study. Issue 1 (25th February 2021) - Giles, Anthony; Williams, Chris; Pugh, Daniel; Bowen, Phil; Marsh, Richard; O'Doherty, Tim
Abstract : Steelmaking is energy intensive, with manufacturing facilities representing some of the biggest point-source carbon dioxide (CO2 ) emitters in the UK. Efficiency improvements are essential with rising energy costs, driving significant investment from the UK iron and steel sector. However, the industry still finds it difficult to justify waste heat recovery (WHR) projects, as individual schemes incorporating waste heat capture and an end-use for the waste heat often incur high capital costs, resulting in long payback times. This paper describes the conceptual and numerical development of a strategy for the deployment of WHR using a large integrated steel works as a case study. An existing asset was utilised to link individual waste heat schemes together with a single end-user; thereby reducing the capital requirement for each subsequent project. The proposed strategy and its development is discussed, followed by the resultant carbon dioxide and energy savings (estimated to be 2.3 Mt and equivalent to £45 million), over the 6-year period since its implementation.